Perbandingan Efektivitas CT scan dan MRI dalam Evaluasi Trauma Kepala: Comparison of the Effectiveness of CT Scan and MRI in the Evaluation of Head Trauma - Nabilah Nur Hasanah; Novia Dwi Amelia Putri; Nuzul Rizky Aulia; Siti Rohimah; Shiva Nayla Putri; Elsa Amelia Nainggolan; Tio Ayu Dor Sihite; Intan Maulina (Elektriese: Jurnal Sains dan Teknologi Elektro, 2026)
Head trauma is an injury caused by impact or mechanical force to the head that causes temporary or permanent brain dysfunction. Rapid and accurate evaluation is essential for determining appropriate treatment. CT scanning is the primary modality in the initial assessment of head trauma due to its widespread availability, speed of examination, and ability to detect acute intracranial hemorrhage. Conversely, MRI provides higher soft-tissue resolution and is highly sensitive for detecting diffuse axonal injury or contusions that are not visible on CT scans. The identification stage was conducted by searching the literature using keywords such as "head trauma," "traumatic brain injury," "CT scan vs MRI," "diagnostic accuracy of CT," and "MRI diffuse axonal injury." The screening process involved selecting articles based on titles and abstracts and excluding duplicates, non-clinical studies, non-scientific journal publications, and studies without quantitative data. Successful articles then proceeded to the eligibility stage with a full-text review to ensure that the studies directly addressed the diagnostic performance of CT scanning and MRI in head trauma cases. This demonstrates the importance of both modalities, each with its own advantages. MRI has higher sensitivity and accuracy in detecting non-hemorrhagic parenchymal lesions such as diffuse axonal injury (DAI), contusions, and microhemorrhages. Conversely, CT scans are superior in detecting acute hemorrhage, skull fractures, and cerebral edema that require immediate treatment. MRI is superior for detecting non-hemorrhagic lesions, but CT remains the first choice in the acute phase. The combination of the two provides the most comprehensive diagnostic evaluation.